A Human Lung Xenograft Mouse Model of Nipah Virus Infection - Valbuena, Gustavo; Halliday, Hailey; Borisevich, Viktoriya; Goez, Yenny; Rockx, Barry (PLoS pathogens, 2014)
Nipah virus (NiV) is a member of the genus Henipavirus (family Paramyxoviridae) that causes severe and often lethal respiratory illness and encephalitis in humans with high mortality rates (up to 92%). NiV can cause Acute Lung Injury (ALI) in humans, and human-to-human transmission has been observed in recent outbreaks of NiV. While the exact route of transmission to humans is not known, we have previously shown that NiV can efficiently infect human respiratory epithelial cells. The molecular mechanisms of NiV-associated ALI in the human respiratory tract are unknown. Thus, there is an urgent need for models of henipavirus infection of the human respiratory tract to study the pathogenesis and understand the host responses. Here, we describe a novel human lung xenograft model in mice to study the pathogenesis of NiV. Following transplantation, human fetal lung xenografts rapidly graft and develop mature structures of adult lungs including cartilage, vascular vessels, ciliated pseudostratified columnar epithelium, and primitive "air" spaces filled with mucus and lined by cuboidal to flat epithelium. Following infection, NiV grows to high titers (10(7) TCID50/gram lung tissue) as early as 3 days post infection (pi). NiV targets both the endothelium as well as respiratory epithelium in the human lung tissues, and results in syncytia formation. NiV infection in the human lung results in the production of several cytokines and chemokines including IL-6, IP-10, eotaxin, G-CSF and GM-CSF on days 5 and 7 pi. In conclusion, this study demonstrates that NiV can replicate to high titers in a novel in vivo model of the human respiratory tract, resulting in a robust inflammatory response, which is known to be associated with ALI. This model will facilitate progress in the fundamental understanding of henipavirus pathogenesis and virus-host interactions; it will also provide biologically relevant models for other respiratory viruses.